CRISPR-Cas9 GENE EDITING: MECHANISMS, CLINICAL APPLICATIONS, AND FUTURE PERSPECTIVES - Porwolik, Hanna; Porwolik, Agata; Szydłowski, Radosław; Cyran, Patryk; Bodera, Magdalena; Kaźmierska, Anna (International Journal of Innovative Technologies in Social Science, 2026)
The system of gene editing known as the CRISPR-Cas9 system has revolutionized the field of gene editing and provides a platform that allows for the modification of genetic sequences with precision and efficiency, having implications for both the basic research of science and for treatments. Its mechanism, which is derived from bacterial adaptive immunity, consists of a guide RNA that leads to specific epigenetic DNA sites a nuclease named Cas, to target it for cleavage; this permits gene correction, inactivation, or insertion. The clinical potential of this technology is enormous with applications ranging from hereditary diseases, oncology, and infectious diseases. Of note too, the approvals from the FDA for therapies targeted at the treatment of sickle cell anemia and beta thalassemia speaks volumes to its transformative effect on what was previously in-treatable conditions. In oncology, the technologies are increasing immunotherapies by engineering T-cells and interfering with immune checkpoints, but also working on viral genomes (e.g. HIV, HBV) and destroying antibiotic-resistance genes in bacteria. However, there are still major challenges such as off-target effects, in vivo delivery efficiency and possible immunogenicity of Cas proteins. Future advancements are dedicated to refine the use of the CRP systems using advanced variants such as base and prime editors, and to extend the toolkit by Cas12 and Cas13 for RNA/DNA targeting, as well as devising innovative delivery systems for overcoming the biological barriers. Ethical, regulatory, and societal considerations are paramount in the continued promotion and progressive growth of this technology.